2018
DOI: 10.1016/j.psyneuen.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and adipokines in women: Study of women’s health across the nation

Abstract: Small clinical studies suggest depression is associated with alterations in adiponectin and leptin, adipocyte-derived secretory proteins involved in metabolic regulation; however, longitudinal data on these association are lacking. This study examined cross-sectional and longitudinal associations of depressive symptoms and major depressive disorder (MDD) with adiponectin and leptin in healthy middle-aged women (mean (SD) age, 45.6 (2.5) years). Cross-sectional analyses included 575 women with baseline adipokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…An association among peripheral adiponectin levels and MDD has been suggested in different populations and health conditions (Table 1). A study consisting of cross-sectional ( n = 575) and longitudinal ( n = 262) analyses has shown that current episode of MDD, symptom severity, and history of depression in middle-aged women were all linked to the low adiponectin levels over a 5-year follow-up [39]. In depressed women, the adiponectin levels were sharply reduced by 25% and remained low over a 24-h period when measured hourly [40].…”
Section: Changes In Peripheral Adiponectin Levels In Patients With Dementioning
confidence: 99%
“…An association among peripheral adiponectin levels and MDD has been suggested in different populations and health conditions (Table 1). A study consisting of cross-sectional ( n = 575) and longitudinal ( n = 262) analyses has shown that current episode of MDD, symptom severity, and history of depression in middle-aged women were all linked to the low adiponectin levels over a 5-year follow-up [39]. In depressed women, the adiponectin levels were sharply reduced by 25% and remained low over a 24-h period when measured hourly [40].…”
Section: Changes In Peripheral Adiponectin Levels In Patients With Dementioning
confidence: 99%
“…[ 9 ] Everson-Rose et al . [ 10 ] reported an association between depressive symptoms and low adiponectin in middle-aged women with MDD, as the combination of adiponectin and C1q activated the classic complement system. [ 11 ] Therefore, C1q plays a role in complement activation, removal of immune complexes and necrotic cells, stimulation of cytokine production, regulation of lymphocyte function,[ 12 ] and emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Adam and colleagues reported that low mood may be significantly related to adiponectin and BMI in premenopausal women but not in postmenopausal women [ 56 ]. Everson–Rose and colleagues reported that the severity of depressive symptoms is significantly associated with lower levels of adiponectin among healthy middle-aged women in both cross-sectional and 5-year follow-up longitudinal analyses [ 57 ]. Although in this analyses, these factors age, adiposity, hormonal and behavioral risk factors (e.g., diet, smoking status, alcohol consumption, and physical exercise), all of which are potentially important confounders have been taken into consideration, the levels of the adiponectin and leptin were highly changed and varied by menopause stages in women at midlife with/without obesity [ 58 ].…”
Section: Discussionmentioning
confidence: 99%